Funny girl [compact disc, unabridged] : a novel - Hornby, Nick (Penguin Audio, 2015)
Set in 1960's London, this is a lively account of the adventures of the intrepid young Sophie Straw as she navigates her transformation from provincial ingenue to television starlet amid a constellation of delightful characters.